(untitled) (Cadernos de Sociomuseologia, 2015)
The article intends to understand what representations about Brazil are found in Portuguese museums. The survey information, document and qualitative ones, was done in 40 museums by as a common visitor who observes and draws conclusions from the information that is offered to him during the visit, even understanding that the exhibits assembly process transcends what it is in sight. It is assumed that the exhibits of the museums help to build representations that are endorsed by a real aura that surrounds them. Among the representations, we have one that shows Brazil as an important provider of wealth for Portugal, which is in the most traditional museums in the country, and another one that presents the two countries historical relationship through some Portuguese characters like Cabral and Pedro I (IV of Portugal), more common mainly in museums located out of the capital. Then, we can see that the close relationship that Brazil had with Portugal as a colony is still helping to build the representations that one country has about the other one. Keywords: Museums; Representations; Portugal; Brazil.